Analisis Kestabilan Lereng Timbunan Tailing Bauksit: Studi Kasus PT. Laman Mining Kecamatan Hilir Utara - Herman; Firman (Politeknosains, 2020)
Bauxite mineral commodities in Indonesia are very abundant, based on Pusdatin data, 2016. Bauxite mineral mining is carried out by the method of selective open mining (surface mining), where in its application this method tends to change the morphology in a fairly large area. PT. Laman Mining is one of the mining companies currently operating in Ketapang Regency, and produces residual deposits. From the research conducted it was found that the tailling disposal angle can be made up to 80 degrees and in model two the level should not exceed 45 degrees with factor of safety 1.398. and tailing residues are also utilized, through compressive strength testing, it is found that sample 1:1 have medium quality and sample 1:2 low quality based on SNI.